Customer Relationship Management ( CRM) in Hotel Industry : A framework Proposal on the Relationship among CRM Dimensions, Marketing Capabilities, and Hotel Performance - Abdul Alem Mohammed; Basri bin Rashid (International Review of Management and Marketing, 2012)
Customer relationship management (CRM) has a growing popularity and is becoming one of the hottest academic and practical topics in the business field. In fact, due to the competitive environment, CRM is crucial and has become a niche for firm performance. However, there is limited research that reveals the relationship between CRM dimensions and hotel performance. Therefore this study is an attempt to provide a value conceptual model that explains the theoretical linkages existing between CRM dimensions and hotel performance. This study serves not only to clarify the relationship between CRM dimensions and hotel performance, but also to explain the mediation role of marketing capabilities in this relationship.